Improving the performance and reproducibility of lead - tin perovskite absorbers toward all-perovskite tandem solar cells - Farrar, MD (2022)
This thesis explores a subset of hybrid perovskites that incorporate tin into their crystal lattice alongside lead. Hybrid perovskite semiconductors have gained global interest over the past decade due to their remarkable optoelectronic properties, and excellent power conversion efficiencies, which now compete with well-established commercial technologies. By incorporating tin, these materials can achieve band gaps far narrower than their pure-lead counterparts. This property makes lead-tin perovskite materials suitable for the construction of all-perovskite tandem solar cells to improve power conversion efficiencies beyond the theoretical limit for a single junction device. Although these materials are promising and have been successfully demonstrated to achieve high power conversion efficiencies, they are still far below their theoretical efficiency and comparatively few studies have been conducted on how to maximise the potential of this class of materials. The work presented in this thesis explores three topics utilising an FA0.83Cs0.17Pb0.5Sn0.5I3 absorber. In the first instance a bulk passivation strategy is investigated with the aim to reduce non-radiative recombination in the absorber material, using several thiocyanate additives that are found to successfully enhance the photoluminescence quantum efficiency of the material and improve charge carrier diffusion length. Proceeding this, the influence that selective contact materials have on non-radiative recombination is explored culminating with a passivation strategy at the interface with the electron transport material. This led to enhanced performance of resulting devices. Chapter 5 details the fabrication of 2T-monolithic tandem solar cells. The successful resolution of fabrication issues, and optimisation of the lead-tin sub-cell generated highly efficient tandem solar cells. The final experimental chapter in this thesis investigates the removal of DMSO from the lead-tin precursor ink due to its ability to oxidise Sn2+ to Sn4+, which can cause detrimental effects within the material. This is achieved by the addition of the ammonium halide salt DMACl. It is shown that highly oriented thin films can be fabricated with enhanced grain sizes leading to a much-improved device stability, in air, of over four times that of the device utilising DMSO.